2014
DOI: 10.1007/s12633-014-9209-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ladder Silsesquioxanes by in situ Polycondensation of Cyclic Tetravinylsiloxanetetraols

Abstract: Functionalized tetrahydroxy-cyclotetrasiloxanes are very attractive precursors of tetrasiloxane ring systems in linear silsesquioxanes (LPSQs). Vinyl groups are especially important since they can be employed for various chemical transformations (e.g. hydrosilylation, metathesis reactions, thiol-ene addition). However, isolation of such highly reactive species bearing small side substituents at silicon atoms with high yield is challenging. We overcame the problem by in situ condensation of 2,4,6,8-tetrahydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…Chemical modification of mica using reactive silanes was also reported [32][33][34][35] . The results are consistent with those already reported 40 by us 41 . We have found that muscovite mica can be easily modified using new linear oligosilsesquioxanes (LPSQ-COOH), functionalized with side 2-(carboxymethylthio)ethyl groups at their doublestrand backbone.…”
Section: Introductionsupporting
confidence: 94%
“…Chemical modification of mica using reactive silanes was also reported [32][33][34][35] . The results are consistent with those already reported 40 by us 41 . We have found that muscovite mica can be easily modified using new linear oligosilsesquioxanes (LPSQ-COOH), functionalized with side 2-(carboxymethylthio)ethyl groups at their doublestrand backbone.…”
Section: Introductionsupporting
confidence: 94%
“…Based on the known literature, [26,36] mechanisms of all transformationsa re illustrated in Figures 5a nd 6. The silylation by HMDS proceeds through the formation of af our-centered transition state and is followed by an ucleophilic attack of oxygen toward the silicon atom in the HDMS molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Although inorganic materials, [19][20][21][22] alcohols, [23][24][25][26][27][28][29][30] phenols, [26][27][28][29] carbohydrates, [29] carboxylic acids, [31] oximes, [32] ande ven thiols [33] have been successfully silylated by various disilazanes, the use of these silylatinga gents in O-metalation of simple silanols and polyhedralo ligomeric silsesquioxane (POSS) silanols has never been comprehensivelys tudied.T herea re only few examples: Lebedeve tal. [36] They tested this reactionu nder many conditions and obtainedt he best resultsi nt oluene at 110 8Ca fter 24 h. Furthermore, Pike investigated the reactionb etween primary silylamines with somes ilanols in the presence of acidic and basic catalysts. [34] However,s ensitive halosilanes were utilized as additional substrates and activators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled intermolecular polycondensation of Ph 4 (HO) 4 Si 8 O 12 will enable the production of an ew ladder-like polysiloxane in as imilar manner to the synthesis of laddersiloxanes from cyclotetrasiloxanes (see Figure S21). [45,46] In addition, when Ph 4 (HO) 4 Si 8 O 12 is silylated with alkoxy(chloro)silanes and subjected to furtheri ntramolecular condensation, stepwise extension of the cage structure can be expected (see Figure S22). Please note that the feasibility of formation of such interesting structures may be low because of the strain of the bond angles.…”
Section: Validity Of the Hydrolysisand Intramolecular Condensation Rementioning
confidence: 99%